Addressing Racism and Its Deeply Entrenched Dynamics: A 21st Century Imperative (Health Equity, 2023)
Throughout the world, extreme nationalism, racism, anti-Semitism, and other forms of ethnic and religious bias are sustained by an antiquated notion that the human family can be divided and ranked based on physical characteristics and ascribed traits. This belief in a hierarchy of human value fuels racism in America, dividing our population and providing platforms for hatred and attacks on our democracy. The foundational fallacy of human hierarchy continues to spur many inequities both consciously and unconsciously through systems and individual acts. As this ill-conceived belief ossifies, divisiveness hardens among communities, creating barriers to unifying our population into a critical mass that is committed to equity in our communities, in our health care, in education, in employment, and all aspects of our society. We must focus our energy, resources, and discourse on uprooting and eliminating the false ideology of a hierarchy of human value and seed what must be valued most: our common humanity. When our beliefs and understandings shift, our capacity for empathetic relatedness, civility, and progress toward achieving common interests will increase. Beliefs, particularly deeply held and hardened beliefs, have a way of influencing, if not shaping, our lives. It is past time to overturn this belief in a hierarchy of human value and address, and redress, its legacy of discriminatory policies and practices that create unhealthy outcomes for people of color. Research reveals that the inequities caused by racism cost our nation almost $2 trillion annually in lost purchasing power, reduced job opportunities, and diminished productivity.1 What is also clear is that the conscious and unconscious belief in a racial hierarchy fuels the reluctance of political leaders and policymakers to acknowledge the inequities and devote adequate resources to addressing them. Our democracy, similar to others around the world, is based upon full human engagement and action on shared interests for the population. Clearly, to move forward, this nation must heal the wounds of our past and learn to work together with civility, and indeed, with love. We must build the individual and collective capacity to ?see ourselves in the face of the other.? We know the stress of racism predisposes the body to chronic illness. Our inability as individuals and as a society to value all human beings equally is making us sick, literally. Even more broadly speaking, the incapacity to value all human beings equally keeps us from experiencing optimal well-being and happiness. Our hearts and brains are designed to resonate within harmonious relationships. The opposite?fear and anxiety, separation, alienation, and hate?induces stress and distress. Distress causes a cascade of illness related changes within our very cells in our physical bodies and within our body politic. Researchers estimate that 265 people die every day from racial health disparities in the United States. But it is not just people of color who suffer and die prematurely.2 The U.S. population, as a whole, lives shorter lives and has poorer health than our peer nations. Our residual belief in a false taxonomy and hierarchy of value is a major contributing factor to our poor health outcomes. Distress responses related directly and indirectly to racial fear, anxiety, and to its attendant social conditions contribute to hypertension and cardiovascular disease, glucose intolerance, insulin resistance, and diabetes and its precursor metabolic syndrome.3 The National Collaborative for Health Equity (NCHE) is committed to addressing the deep racial and ethnic inequities that adversely affect the health of men, women and children living in communities of color. Our mission is to dismantle racism through three intervention areas: supporting local leaders, providing and facilitating data that help create authentic narratives, and supporting grassroot efforts that are engaging racism on the ground at the local level. With the support of our funders, NCHE provides institutions and leaders from historically marginalized and excluded communities with tools to improve the social, economic, and environmental conditions that shape health. These tools include leadership development, policy analysis, data mining and analysis, and community organizing and mobilization to address a range of issues that are the ultimate determinants of health. We are committed to addressing the deep racial and ethnic health inequities that persist largely due to structural and institutional racism and exclusion. Furthermore, NCHE places a priority on supporting and connecting leaders in communities that are creating the change America so badly needs. Since the first European settlers arrived on our shores centuries ago, American culture has placed the relative worth of White people above all others, and at times violently enforced this. The adopted and embedded mindset and belief have restricted the quality of life for people of color, whereas limiting opportunities for success and preventing the realization of the full potential of our democracy. America's history includes enslaving people, committing genocide among the Indigenous population, and embracing centuries of institutionalized racism. Yet, unlike other countries that have endured war, sectarian, or racial strife, the United States has never established a comprehensive Truth and Reconciliation Commission effort to heal divisions and bring equal opportunities to all communities. As a result of the unequal conditions caused by structural racism and discriminatory policies and practices, the nation experiences a significant wealth gap between White people and families of color, persistent residential segregation, unequal access to quality health care and affordable housing, achievement gaps in education, and discrimination in hiring practices. In fact, the 2021 Survey of Income and Program Participation found that the median White family has 12 times the amount of wealth of the median Black family, a disparity translating to $18,430 of median net worth for Black households compared with $217,500 in median net worth for White households.4 Truly, America has two societies, one predominantly White and privileged, and another Black and Brown where daily struggles for health care, food, housing, jobs, and other social determinants of health exist. In 2016, under the guidance of Dr. Gail Christopher, the W.K. Kellogg Foundation launched Truth, Racial Healing & Transformation (TRHT), a national and community-based effort to engage communities, organizations, and individuals from multiple sectors across the United States in racial healing and addressing present-day inequities linked to historic and contemporary beliefs in a hierarchy of human value. A year-long design process was informed by 176 community and civic leaders, scholars, and practitioners. The TRHT framework seeks to jettison the belief in a hierarchy of human value by centering transformative approaches to community-based healing and supporting the pursuit of actionable change. It has been implemented in an array of communities, including >70 college and university campuses. At NCHE, our initiatives and programs are all grounded by the TRHT framework, which include five pillars that guide communities and organizations in implementing TRHT-driven initiatives. Narrative Change examines how to create a more complete and accurate narrative that will help people understand how racial hierarchy has been embedded in our society from the beginning. Racial Healing and Relationship-Building focuses on ways for all of us to heal from the wounds of the past and build mutually respectful relationships across racial and ethnic lines that honor and value each person's humanity. Separation examines and finds ways to address segregation, colonization, and concentrated poverty in neighborhoods. Law reviews discriminatory civil, criminal, and public policies, and seeks solutions that will produce a more just application of the law. Economy studies structured inequality and barriers to economic opportunities and developing solutions that will create a more equitable society. Today, NCHE is proud to present our inaugural group of NCHE Senior Scholars, five distinguished academic and social justice leaders, who have each written comprehensive articles that align with the TRHT pillars. Their knowledge and insights will be shared with the NCHE network through publications, webinars, and this special roundtable event with Health Equity, a peer-reviewed journal that is NCHE's official publication partner. We will all benefit from having access to the expertise and insights that these scholars can provide as NCHE continues its mission to advance health equity in communities of color. The Senior Scholars, who you will learn more about shortly, are as follows: